Freedom as a main principal of activity of epistolary of Olena Pchilka - Оніпко, В’ячеслав Федорович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
Olena Pchilka was a famous personality of cultural and enlightening movement of the end of the 19 th and the beginning of the 20 th centuries. The author pays attention to the place of the epistolary heritage of the writer in contemporary literary criticism. In the article it is said about the role of freedom in Olena Pchilka’s life. She is described as a fighter for the national freedom and the defender of freedom of the creator. On the example of Olena Pchilka’s letters there are described several aspectsof activity of the Russian empire and Galichina authorities as for the Ukrainian word.The problem of author’s freedom is revealed concerning unauthorized changes in works of the writer by other ways and what kind of damage they cause. Here in the article is shown the fight of Olena Pchilka with royal censorship for cancelling fonded decrees, that forbade the Ukrainian language. Such conclusions were made that freedom was the background of the creative process of the writer and the basis of her cultural and public outlook.